Challenges and Prospects of Youth Entrepreneurship in Dhangadhi Sub-Metropolitan City, Nepal - Bhatta, Ghanshyam; Baijal, Sanjay (KMC Journal, 2024)
Youth entrepreneurs are the driving forces of business innovation enhancing the economic development and transformation of the society. This study investigates the challenges and prospects of youth entrepreneurship in Dhangadhi Sub-metropolitan city, Nepal. Employing a descriptive survey research design of quantitative method, the data were collected through structured questionnaire and analyzed using descriptive statistical tools. 56 respondents were selected using purposive sampling method among young entrepreneurs. The study found that the main reason to start business is being self-dependent followed by upgrading income level. Regarding the challenges of young entrepreneurship, it is found that competition is the main challenge followed by access to finance. However, the major prospects are opportunity of micro enterprises, innovation and creativity, development of entrepreneurial skills, building enterprising culture and economic participation. The government should build up business environment to use their ideas, methods, skills and abilities for entrepreneurship development through flexible rules and regulations and financial supports. This study could be a milestone for future researchers, policy makers, academician, owners and youth entrepreneurs.